Measuring consumers' preferences of stingless bee honey (meliponine honey) based on sensory characteristics - Saludin, Siti Farhana; Kamarulzaman, Nitty Hirawaty; Ismail, Mohd Mansor (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2019)
Nowadays, stingless bee honey (meliponine honey) or locally known as ‘madu lebah kelulut’ is becoming popular among Malaysian consumers due to its acclaimed health benefits and advantages such as antioxidant and anti-inflammatory activities. Usually, stingless bee honey is used as a supplement to modern medicine, and the increase in health awareness among consumers has also increased the demand for stingless bee honey. However, due to the low production of stingless bee honey in the local market, Malaysia continues to import honey from other countries. As there is an abundant of imported honey products, local beekeepers are facing stiff competition, and consumers also need to make a difficult purchasing decision on the most preferable honey products in the market. Therefore, the main objective of the present work was to determine the consumers’ quality preferences towards stingless bee honey based on sensory characteristics. A total of 406 respondents of honey consumers were selected to test stingless bee honey sample based on its appearance, aroma, texture and flavour. The respondents responded based on a structured questionnaire using a 5-point Likert scale statements about their responses towards stingless bee honey sensory characteristics. The responses of the respondents were analysed based on descriptive analysis, factor analysis and logistic regression analysis. The results revealed nine factors that influenced consumers’ preferences towards stingless bee honey such as granularity, colour, bitterness, sweetness, viscosity, spice aroma, sourness, herbal aroma and fruity aroma, with viscosity being the most influential factor. The present work concluded that sensory characteristics were important to determine the consumers’ quality preferences towards stingless bee honey on purchasing decision.